Meridional heterogeneities (according to magnetotelluric studies) on the territory of the Dnieper-Donets Basin - Logvinov, I.M.; Tarasov, V.N. (Reports of the National Academy of Sciences of Ukraine, 2017)
On the basis of a two-dimensional magnetotelluric inversion data, 3 quasimeridional conduction zones (CZs) crossing the Dnieper-Donets Basin are identified. In depth, the conducting objects are located on sedimentary rocks up to 70 km and more. Spatially, CZs are consistent with regional tectonic zones activated at different times up to today. On the Dnieper graben, the zones control the location of oil, oil-gas, and oil-gas-condensate fields. To the east from CZs, only gassy mines are mainly available. The results can be used to confirm the hypothesis that hydrocarbon deposits are associated with zones of generation and transport of hydrocarbon-containing fluids located right up to the mantle.